Spatio‐Temporal Variations in Carbon Isotope Discrimination Predicted by the JULES Land Surface Model. Issue 12 (8th December 2022) - Palmer, Lewis; Robertson, Iain; Lavergne, Aliénor; Hemming, Deborah; Loader, Neil J.; Young, Giles; Davies, Darren; Rinne‐Garmston, Katja; Los, Sietse; Williams, Jamie
Abstract: Stable carbon isotopes in plants can help evaluate and improve the representation of carbon and water cycles in land‐surface models, increasing confidence in projections of vegetation response to climate change. Here, we evaluated the predictive skills of the Joint UK Land Environmental Simulator (JULES) to capture spatio‐temporal variations in carbon isotope discrimination (Δ 13 C) reconstructed by tree rings at 12 sites in the United Kingdom over the period 1979–2016. Modeled and measured Δ 13 C time series were compared at each site and their relationships with local climate investigated. Modeled Δ 13 C time series were significantly correlated ( p < 0.05) with tree‐ring Δ 13 C at eight sites, but JULES underestimated mean Δ 13 C values at all sites, by up to 2.6‰. Differences in mean Δ 13 C may result from post‐photosynthetic isotopic fractionations that were not considered in JULES. Inter‐annual variability in Δ 13 C was also underestimated by JULES at all sites. While modeled Δ 13 C typically increased over time across the UK, tree‐ring Δ 13 C values increased only at five sites located in the northern regions but decreased at the southern‐most sites. Considering all sites together, JULES captured the overall influence of environmental drivers on Δ 13 C but failed to capture the direction of change in Δ 13 C caused by air temperature, atmospheric CO2 and vapor pressure deficit at some sites. Results indicate that the representation of carbon‐water coupling in JULES could be improved to reproduce both the trend and magnitude of interannual variability in isotopic records, the influence of local climate on Δ 13 C, and to reduce uncertainties in predicting vegetation‐environment interactions. Plain Language Summary: Carbon has two stable isotopes, 12 C and 13 C. During the diffusion of carbon dioxide through the stomata of C3 plants, the lighter carbon isotope ( 12 C) diffuses more easily resulting in leaf internal air that is depleted in 13 C compared to the ambient air. Tree rings record this discrimination against 13 C (noted Δ 13 C) which is used to decipher information about past climates, including atmospheric CO2 concentration when the rings formed. The Joint UK Land Environment Simulator (JULES) is a land‐surface model that predicts environmental processes (e.g., the carbon and water cycles). Comparing JULES estimates of Δ 13 C with tree‐ring measurements helps to improve simulations, leading to more accurate projections of ecosystem functioning under different climates. We found that JULES accurately predicted tree‐ring Δ 13 C in 8 out of 12 UK sites over a 38‐year period, with offsets in mean values of up to 2.6‰, but underestimated interannual variations in Δ 13 C at all sites. JULES captured the influence of environmental changes on tree‐ring Δ 13 C relatively well, although the trees' responses at individual sites varied. Results suggest that improvements are needed in JULES to reduce uncertainties in predicting the carbon and water cycles and therefore to produce more accurate projections of future climate‐vegetation interactions. Key Points: Joint UK Land Environmental Simulator (JULES) predicted well the tree‐ring Δ 13 C of oaks in eight out of 12 UK sites but underestimated inter‐annual variations and mean values JULES captured the environmental drivers of Δ 13 C, but the model failed to reproduce the direction of change in Δ 13 C at some individual sites More tree‐ring chronologies are needed to improve understanding of spatio‐temporal changes in Δ 13 C for UK broadleaf deciduous trees